IMPROVING THE OPERATION OF TRANSPORT BUS FLEETS TAKING INTO ACCOUNT THE DEVELOPMENT - Avliyokulov J. S.; Sharapov Z. Z.; Tajiev R. D. (Journals Park Publishing, 2022)
Passenger transport as a necessary component of human civilization is of great importance in the economic and social development of society. This type of transport, as an important element of social progress, has always had a certain state support, which is largely due to the specific features and conditions of management in this sector. In such conditions, the problem of balanced and most efficient use of the public transport system becomes extremely relevant, and its solution requires the use of the most modern subtasks and methods.